Organizational Culture and Self-Efficacy with Work Motivation and Leadership as Key Factors - Wahyul Huda; Tri Joko Raharjo; Erni Suharini; Titi Prihatin (Qubahan Academic Journal)
To examine these relationships in a school setting, this study investigates the effects of organizational culture on teacher performance directly using leadership and work motivation as mediators and ‘self-efficacy’ variables. Using primary data from the educators of different universities, we apply an Agenda based Structural Equation Model (SEM) by using SmartPLS 2024. Results featured highlighted strong positive correlations where organizational culture and self-efficacy directly impact on teacher performance, along with work motivation acting as a significant mediate between these links. The above findings are significant as the relationship between leadership and work motivation were identified to be among essential drivers of teacher performance which can lead to an indication that effective leadership yields high motivational levels with educators. The inter-relatedness of these constructs suggests the value in nurturing a supportive organization culture and effective leadership to positively affect educational outcomes. The study concludes with a focus on the importance of education policymakers to set up environments that promote teacher motivation and performance, thus positively affecting students’ experience in schools the ultimate beneficiaries.